Pembungkaman Pers Pada Masa Orde Baru (Refleksi Filosofis atas Kebebasan Pers Indonesia Masa Orde Baru) - Murtiningsih, Rr. Siti; Siswanto, Joko (Jurnal Filsafat "WISDOM", 1999)
The research wants to describe the condition of press stifling in the New Orde. Then, it tries make a philosophical reflection about the condition of arangement and practical standart of jurnalism in Indonesia post New Orde.The research uses the "philosophical-hermeneutics" method. At the second stage, data are analyzed by philosophical reflection about the stifling of press in the New Orde. The data are collected by library inquiry.The result of this research are: at the end of New Orde regime, the stifling of press and the controling of press are still done. Threfore, there is no space for the press freedom at the time. The press freedom is the symbol of democration. The probelm of democration is really the only press freedom. It will be an agenda of probelm when we require the democratization in large scale. However, without some press freedom there is no ooportunity to get dome democration. It is the significant meaning of press freedom for attempting a democratization.